Biochemical composition of whole seed, decorticated seed and seed coat in sesame (Sesamum indicum L.) of different seed coat colours: BIOCONTROL COMPOSITION OF WHOLE SEED, DECORTICATED SEED AND SEED COAT IN SESAME - SEEMA PAROHA,; APOORVA BHARGAV,; ANJAY TRIPATHI,; SUBHASHSHRI GARG,; VIRENDRA KAWRETI,; A R G RANGANATHA, (Journal of Oilseeds Research, 2014)
Biochemical analysis of whole seed, decorticated seed and seed coat of different coloured varieties of sesame were studied. Maximum oil content in whole and decorticated seed was recorded in white seeds (47.5 and 51%, respectively). Light brown seed coat showed maximum oil content (15.0%). Minimum free fatty acid (FFA) content in whole seed was recorded in white seeds (0.62%) and maximum in dark brown seeds (1.71%). The decorticated black seed contained minimum FFA content (2.13%), white seed coat the lowest (0.85%). Highest FFA content in the seed coat was exhibited by light brown seeds (1.96%). Minimum oxalic acid in whole seeds was in white (0.82%). The white and dark brown decorticated seeds contained minimum oxalic acid (0.88%). Seed coat of all the varieties viz., black (2.65%), light brown (2.15%), dark brown (2.10%) and white (1.84%) exhibited the higheroxalic acid than whole and decorticated seed. The highest protein was found in whole and decorticated seed of white (18.35 and 16.45%, respectively), whereas seed coat of all the varieties contained one-fourth protein content of the whole and decorticated seeds. White (5.60 mg/kg) and black (5.65 mg/kg) seeds were found almost at par for desirable sesamol, an antioxidant, in whole seed. The decorticated seed of black (6.35 mg/kg) and white (6.15 mg/kg) seeds of sesame exhibited the highest sesamol, whereas the maximum of 6.95 mg/kg in white seeds.